Adoption of Wearable Technology (Smartwatch) for Health Monitoring: Opportunities and Marketing Strategies - Azzahrah Putri Haykal; Usep Suhud; Setyo Ferry Wibowo (Greenation International Journal of Economics and Accounting, 2025)
This qualitative study explores the role of smartwatches in supporting body health by examining user perceptions and experiences. With the advancement of wearable technology, smartwatches have become increasingly popular not only as communication tools but also as health monitoring devices. This research focuses on identifying the benefits and challenges associated with using smartwatches to monitor physical activity, heart rate, sleep patterns, and other health-related metrics. Data were obtained through literature review and observation of user behavior, emphasizing the subjective understanding of how smartwatch features contribute to health awareness and lifestyle changes. The study concludes that smartwatches can significantly aid in promoting healthier habits and preventive healthcare when used consistently and consciously. However, technological limitations and user dependency may affect their effectiveness. This research provides valuable insights into the integration of digital health tools in everyday life and their implications for personal health management.